PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI PENGGUNAAN LKPD BERBASIS KONTEKSTUAL PESERTA DIDIK KELAS IV SD MAITREYAWIRA PALEMBANG - Sepvani Putri Lestari; Susy Amizera; Juliana S (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on the results of field observations, several problems were found, including low student learning outcomes, lack of student activity in the learning process, and the use of teaching materials that were less interesting to learn. This study aims to describe the application of contextual-based LKPD in an effort to improve student learning outcomes in the Indonesian language subject. The method used is Classroom Action Research (CAR) which includes the stages of planning, implementation, observation, and reflection. Data were analyzed descriptively through the calculation of averages and percentages. Learning completion criteria were determined based on individual and classical completion. The results of the study showed an increase in learning completion in each cycle, which was 64% in cycle I, and increased to 89% in cycle II. Based on these results, it can be concluded that the use of contextual-based LKPD is effective in improving the learning outcomes of grade IV students in elementary schools.